The southwest monsoon over the subcontinent of India) Pakistan and Bangladesh-A survey - HUQ, M. S. (MAUSAM, 1978)
A synoptic study of the southwest monsoon over the subcontinent of India, Pakistan and Bangladesh has been made for 10 years and a study of different literatures on the subject has also been made. Efforts have been made in this paper to describe, in brief, the widely accepted ideas and some proposed ideas on the subject under the headings: (1) Meaning, causes and burst of the monsoon, (2) Climatological features of the monsoon over the subcontinent- Major wind and temperature systems, (3) Synoptic features of the monsoon over the subcontinent-Heat low, orographic effects, the monsoon trough, easterly waves, monsoon depressions and storms, (4) Cloud information furnished by Radar and Meteorological Satellites during the monsoon, (5) Variability of the monsoon, (6) Forecasting problems during the southwest monsoon of the subcontinent-Forecasting the onset of the monsoon, heavy /very heavy rainfall, persistent monsoon activity with light to moderate rain, breaks in the monsoon, withdrawal of the monsoon, (7) Medium-range and long-range forecast of monsoon rain over the subcontinent and (8) Concluding remarks-Some notable features of the monsoon of the subcontinent. A few maps, figures and diagrams have been appended to make the paper self-explaining various observed and proposed meteorological conditions of the atmosphere.